2017
DOI: 10.1038/s41598-017-01250-0
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional substrate of label-free electrochemical immunosensor for ultrasensitive detection of cytokeratins antigen 21-1

Abstract: Poly(thionine)-Au, a novel multifunctional substrate with excellent redox signal, enzyme-like activity, and easy antibody immobilisation, was synthesised using HAuCl4 as the oxidising agent and thionine as the monomer. The prepared poly(thionine)-Au composite exhibited an admirable electrochemical redox signal at −0.15 V and excellent H2O2 catalytic ability. In addition, gold nanoparticles in this composite were found to directly immobilise antibodies and further improve conductivity. In addition, a label-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It could be obviously seen that in the synthesized nanomaterial, PtNPs were homogeneously distributed on the surface of the NGE, leading to more roughness and wrinkles, which greatly improved the electroactive surface (Figure B). After conjunction with MIP through electropolymerization, the thionine-PtNP-NGE was covered by a dense membrane with flexural nanostrips (Figure C), proving the successful synthesis of the poly­(thionine) (MIP) film through the –NH– bridge . The structure of the NGE, thionine-PtNP-NGE and MIP/thionine-PtNP-NGE were also characterized by SEM (Figure S1, Supporting Information, SI).…”
Section: Resultsmentioning
confidence: 84%
“…It could be obviously seen that in the synthesized nanomaterial, PtNPs were homogeneously distributed on the surface of the NGE, leading to more roughness and wrinkles, which greatly improved the electroactive surface (Figure B). After conjunction with MIP through electropolymerization, the thionine-PtNP-NGE was covered by a dense membrane with flexural nanostrips (Figure C), proving the successful synthesis of the poly­(thionine) (MIP) film through the –NH– bridge . The structure of the NGE, thionine-PtNP-NGE and MIP/thionine-PtNP-NGE were also characterized by SEM (Figure S1, Supporting Information, SI).…”
Section: Resultsmentioning
confidence: 84%
“…19 Wang et al (2017) used a novel nanocomposite of multifunctional poly(thionine)-Au and found a wide detection limit of 4.6 fg mL −1 . 20 Pachauri et al (2018) reported cerium oxide nano-cubes (ncCeO 2 ) with a reduced graphene oxide (RGO)-nanocomposite and found a detection limit of 0.625 pg mL −1 . 21 One newly reported novel biomarker, TP-53, is also targeted for OC detection.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of sensor usually requires redox probes in the electrolyte solutions to generate amperometric signal that is proportional to the formed antigen/antibody complexes. 10 However, one of the main disadvantages of this method is time consuming and labor intensive. 11 Recently, redox probe-free platforms have been developed for immunosensors.…”
Section: Introductionmentioning
confidence: 99%